2018
DOI: 10.1111/jbi.13160
|View full text |Cite
|
Sign up to set email alerts
|

The island rule: An assessment of biases and research trends

Abstract: Aim: The island rule has been widely applied to a range of taxonomic groups, with some studies reporting supporting evidence but others questioning this hypothesis.To bring more clarity to this debate, we conducted a comparative analysis of the available literature, focussing on potential biases. Location: Worldwide.Methods: We performed a systematic review to identify studies testing the island rule and translated these studies' outcomes, so that they follow a consistent approach.The studies were assessed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 72 publications
(116 reference statements)
2
45
1
2
Order By: Relevance
“…The highly inconsistent results of these studies (e.g. 5,6,24 ) are perhaps unsurprising because they typically deal with single species or pool together data on different traits from numerous sources without controlling for variation in study design or accounting for measurement error. Accordingly, a recent systematic review based on a simplified scoring system 24 concluded that previous studies were undermined by author-related biases and that empirical support for the island rule is generally low, particularly for non-mammalian taxa.…”
Section: Introductionmentioning
confidence: 99%
“…The highly inconsistent results of these studies (e.g. 5,6,24 ) are perhaps unsurprising because they typically deal with single species or pool together data on different traits from numerous sources without controlling for variation in study design or accounting for measurement error. Accordingly, a recent systematic review based on a simplified scoring system 24 concluded that previous studies were undermined by author-related biases and that empirical support for the island rule is generally low, particularly for non-mammalian taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Explanations for the island rule are complex and multifaceted, and they include foraging-preference shifts, character displacement, reduced resource competition, and reduced predation pressure (Clegg and Owens 2002;Scott et al 2003). The island rule for birds is inconsistently supported (Gaston and Blackburn 1995;Clegg and Owens 2002;Lomolino 2005;Olson et al 2009;Lokatis and Jeschke 2018), and in mammals endemic to Madagascar there is little evidence supporting this pattern (Kappeler et al 2019). Furthermore, Madagascar is considered by some as a subcontinent rather than an island due to its large land mass (de Wit 2003), such that the Madagascar Jacana may not constitute a true island endemic.…”
Section: Reversed Sexual Size Dimorphismmentioning
confidence: 99%
“…Therefore, if jacanas represent a large-sized species (as do rails, ducks and ratites, according to Lomolino [2005]), the larger size of the Madagascar Jacana compared with the African Jacana is evidence against the island rule. The inconsistencies in findings between studies testing this rule could also be attributable to methodological differences and specific ecological traits that shift the strength of the rule (Clegg and Owens 2002;Lokatis and Jeschke 2018).…”
Section: Reversed Sexual Size Dimorphismmentioning
confidence: 99%
“…Several ‘rules’ have been proposed to describe the patterns of size variation in animal species (Lomolino et al ., ; McNab, ). Among those, the Bergmann's rule is one of the most debated (Blackburn, Gaston & Loder, ; Raia & Meiri, ; Lokatis & Jeschke, ). The Bergmann's rule states that, within closely related endotherm taxa, body size tends to decrease from colder to warmer climates The (Bergmann, ; Salewski & Watt, ; Stanchak & Santana, ).…”
Section: Introductionmentioning
confidence: 99%